Unscrambling mixed elements using high angle annular dark field scanning transmission electron microscopy. - van den Bos, K; De Backer, A; Martinez, G; Winckelmans, N; Bals, S; Nellist, P; Van Aert, S (American Physical Society, 2016)
The development of new nanocrystals with outstanding physico-chemical properties requires a full three-dimensional (3D) characterization at the atomic scale. For homogeneous nanocrystals, counting the number of atoms in each atomic column from high angle annular dark field (HAADF) scanning transmission electron microscopy (STEM) images has been shown to be a successful technique in order to get access to this 3D information. However, technologically important nanostructures often consist of more than one chemical element. In order to extend atom counting to heterogeneous materials, a new atomic lensing model is presented. This model takes dynamical electron diffraction into account and opens up new possibilities to unravel the 3D composition at the atomic scale. Here, the method is applied to determine the 3D structure of Au@Ag core-shell nanorods, but it is applicable to a wide range of heterogeneous complex nanostructures.